THE ROLE OF COUNSELING AND ISLAMIC COMMUNICATION IN CLIENT RECOVERY EFFORT AT THE NATIONAL NARCOTICS AGENCY REHABILITATION CENTER (BNN)TANAH MERAH-SAMARINDA - RUDY HADI KUSUMA; SRI AYU RAYHANIAH (Al-Tazkiah : Jurnal Bimbingan dan Konseling Islam, 2022)
Many cases of drug abuse in Indonesia, so it requires medical and social rehabilitation services in their recovery efforts. Among the services performed are addiction counseling and religious mental coaching applied in Bareta. The purpose of this study is to analyze the client's communication behavior, the role of counseling communication and Islamic communication in the client's recovery efforts, obstacles as well as solutions in carrying out those roles. This type of research is qualitative with a narrative approach. Primary data sources are addiction counselors/assistant counselors, mental builders, and clients. While the secondary data sources are various documents belonging to Bareta. Data collection techniques are interviews, observations, and documentation. The results of the study are that there are many unusual communication behavior factors from clients such as addictive substance factors, individual innate factors, and client confidence. The role of Islamic counseling and communication in client recovery efforts in Bareta is very large because the main weapon for conducting counseling and religious mental coaching is the ability to build professional communication that is therapeutic to the client.